DEVELOPING A FORMAL AND INTEGRATED RISK MANAGEMENT FRAMEWORK IN THE HIGHER EDUCATION SECTOR: A case study on the University of Nottingham - Abdul Halim, Kameel (2007)
The UK is home to some of the world's best universities and indeed boasts one of the world's most highly renowned higher education sectors. Its universities excel in research, teaching and continue to attract students from around the globe and its cities offer ideal infrastructure for learning and student living. Nevertheless the hallowed halls of British universities have not escaped challenges brought on by more difficult operating conditions, regulatory pressure and globalisation and ultimately, increasing uncertainties. As changes in the operating landscape heighten risk elements considerably, universities now increasingly look towards improving their internal capabilities and resources to better manage these risks. Be that as it may, the acceptance and implementation by individual universities of managing risk in an integrated fashion is still heterogeneous where only a few have implemented.